Harnessing Colon Chip Technology to Identify Commensal Bacteria That Promote Host Tolerance to Infection - Gazzaniga, Francesca S.; Camacho, Diogo M.; Wu, Meng; Silva Palazzo, Matheus F.; Dinis, Alexandre L. M.; Grafton, Francis N.; Cartwright, Mark J.; Super, Michael; Kasper, Dennis L.; Ingber, Donald E. (Frontiers in Cellular and Infection Microbiology, 2021)
Commensal bacteria within the gut microbiome contribute to development of host tolerance to infection, however, identifying specific microbes responsible for this response is difficult. Here we describe methods for developing microfluidic organ-on-a-chip models of small and large intestine lined with epithelial cells isolated from duodenal, jejunal, ileal, or colon organoids derived from wild type or transgenic mice. To focus on host-microbiome interactions, we carried out studies with the mouse Colon Chip and demonstrated that it can support co-culture with living gut microbiome and enable assessment of effects on epithelial adhesion, tight junctions, barrier function, mucus production, and cytokine release. Moreover, infection of the Colon Chips with the pathogenic bacterium, Salmonella typhimurium, resulted in epithelial detachment, decreased tight junction staining, and increased release of cytokines (CXCL1, CXCL2, and CCL20) that closely mimicked changes previously seen in mice. Symbiosis between microbiome bacteria and the intestinal epithelium was also recapitulated by populating Colon Chips with complex living mouse or human microbiome. By taking advantage of differences in the composition between complex microbiome samples cultured on each chip using 16s sequencing, we were able to identify Enterococcus faecium as a positive contributor to host tolerance, confirming past findings obtained in mouse experiments. Thus, mouse Intestine Chips may represent new experimental in vitro platforms for identifying particular bacterial strains that modulate host response to pathogens, as well as for investigating the cellular and molecular basis of host-microbe interactions.